Peran sistem informasi akuntansi dalam rangka meningkatkan kinerja karyawan divisi purchasing di PT Semen Indonesia Distributor - Febyanti, Alfiana; Suwarno, Suwarno (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
This study aims to analyze the impact of the Accounting Information System (AIS) on the performance of employees in the purchasing division at PT Semen Indonesia Distributor. Using the Technology Acceptance Model (TAM) approach, the study identifies that perceptions of the ease of use and usefulness of AIS significantly contribute to improving efficiency, speed, and accuracy in work processes. Data were collected through a questionnaire and analyzed using the Partial Least Squares (PLS) method. The results indicate that AIS positively impacts employee performance, contributing 93.4% to the variability in performance. The effective implementation of AIS reduces manual errors, accelerates decision-making, and enhances inter-departmental collaboration. This study recommends employee training, increased automation, and better integration between departments to maximize the benefits of AIS.